2018
DOI: 10.47802/amet.2018.32.17
|View full text |Cite
|
Sign up to set email alerts
|

Surse de sare și procesul de neolitizare din SE Transilvaniei

Abstract: Archaeological investigations at Rupea in the summer of 2018 showed that in the vicinity of each spring of salt water, from about 50 m to 1,7 km there is an early Neolithic site, belonging to Starčevo – Criş. Analyzing the ceramic materials from a complex and those discovered on the area of the site we found that they belong to the Starčevo-Criş III phase. Chronological and cultural links suggest that these communities are related to the discoveries of Cristian III in the same cultural phase. Based on ethno-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the center of Rupea there is the Ethnography Museum "Gheorghe Cernea", subordinated to the Ethnography Museum of Brasov [49]. On the urban perimeter of Rupea and in the vicinity of the town, recent archaeological research has revealed several traces of old habitation, from the Paleolithic [50], Neolithic [51][52][53], Eneolithic [51,[54][55][56][57][58][59], Bronze Age [51], Iron Age, up to the period of the Dacian kingdom, and the period after the conquest of Dacia by the Romans [60]. These findings could be promoted as points of interest for thematic hikes in the near future.…”
Section: Rupea Area-history and Touristic Sightsmentioning
confidence: 99%
“…In the center of Rupea there is the Ethnography Museum "Gheorghe Cernea", subordinated to the Ethnography Museum of Brasov [49]. On the urban perimeter of Rupea and in the vicinity of the town, recent archaeological research has revealed several traces of old habitation, from the Paleolithic [50], Neolithic [51][52][53], Eneolithic [51,[54][55][56][57][58][59], Bronze Age [51], Iron Age, up to the period of the Dacian kingdom, and the period after the conquest of Dacia by the Romans [60]. These findings could be promoted as points of interest for thematic hikes in the near future.…”
Section: Rupea Area-history and Touristic Sightsmentioning
confidence: 99%